Pengaruh Pembelajaran Discovery Learning terhadap Kemampuan Berpikir Kritis Peserta Didik Ditinjau dari Motivasi Belajar - Elga Azmala Putri; Yanti Mulyanti; Aritsya Imswatama (Jurnal Tadris Matematika, 2018)
This study’s aim is to find out experimentation of discovery learning model and direct learning model to critical thinking ability in terms of learning motivation of learners in quadrilateral and triangle mater. The method used in this study is quantitative in the form of quasi experiments. Instruments in this study are critical thinking skills tests presented in the form of post-test, learning motivation questionnaire and observation sheet. Hypothesis test analysis in this research is anava test of two cell road is not equal to the significant level α = 5%. Based on the research results can be concluded that: (1) There is a difference of critical thinking ability between learners using discovery learning model with learners using direct learning model; (2) There is a difference of critical thinking ability of learners who have high learning motivation with learners who have low learning motivation.